EFFEKTIFITAS PEMBELAJARAN DARI RUMAH DENGAN MENGGUNAKAN VIDEO CONFERENCE PADA WHATSAPP TEMA 2 DI TENGAH PANDEMI COVID-19 PADA SISWA KELAS III: SDN AJUNG 02 KALISAT JEMBER - RIMBA ROBUSTIYANI (Mitra Pendidikan, 2022)
In order to elimanate the spread of the corona virus, the government has made a social distancing policy as known as social distancing. This policy also applies to the of education. In this case, the education never guess the COVID-19 would have a very significant impact on teaching and learning activities. So there were no special designs of models or applications for distance learning. However, The schools suddenly stops konvensional teaching and learning process in Indonesia. The solution, students will learn learning from home or known as distance learning SDN Ajung 02 Kalisat which is located at Jalan PB Thamrin 02 Ajung Kalisat which has students from the Ajung, Kalisat and surrounding areas, almost all of students parents are familiar with Android so that it is possible to conduct online learning for teachers and students, such as Google forms, Google Docs , Youtube, and Zoom and Whatsapp. Distance learning is carried out using WhatsApp social media because the institution considers that internet access and students facilities are not the same. This social media was chosen so that students, parents, and educators feel comfortable or not too much cost and spend data quota The purpose of the study was to obtain an overview of the effectiveness of online learning for Third grade of SDN Ajung 02 Kalisat Jember as an effort to eliminate the spread of COVID-19 in the school environment. The research subjects were third grade students. Data were collected by interview via video conference on whatsapps . The study was conducted by first conducting a survey to students regarding the application of online learning.